Graduate Teacher Training in the U.S.: Snapshots from the landscape - Michele DiPietro; Amy M. Buddie (Universitat Politècnica de València, 2013)
The U.S. does not have a federal certification for teaching at the university level mandating graduatelevel training in pedagogy. Nevertheless, the field of Graduate Assistant Training is thriving in America and has produced several models that fit a variety of institutional contexts. This chapter reviews training models at 3 institutions: Kennesaw State University, Carnegie Mellon University, and University of Colorado-Boulder. From these models, we extrapolate common successes and point out some unresolved issues that characterize the U.S. landscape.